Adaptive Lighting System for Presence Detection and Indoor Room Brightness Control - Galina, Mia; Harryanto, Joana Victorine (Jurnal Teknologi dan Sistem Komputer, 2022)
According to the survey, 10% of the electricity used is for lights. Adaptive lighting is a term used to describe innovations that reduce energy consumption for lighting. Generally speaking, adaptive lighting is a highly developed system built with built-in sensors to react automatically without the assistance of the people to make a decision. The research aims to develop an adaptive lighting system with two main functions presence detection and fuzzy logic implementations for automatic brightness adjustments. Increased sensitivity in detecting the presence and movement of items, monitoring the lighting conditions in the room, and consideration of the system's energy efficiency, which was not the main emphasis of the previous study, are some improvements over earlier studies. The device was tested for five days to calculate the energy consumption efficiency of a 4.5 W bulb for 10 hours in total. With a 98.4 % accuracy rate, the adaptive lighting system has proven 74% more efficient than regular lighting.